Geodetic mass balance of surge‐type Black Rapids Glacier, Alaska, 1980–2001–2010, including role of rockslide deposition and earthquake displacement. Issue 12 (14th December 2016) - Kienholz, C.; Hock, R.; Truffer, M.; Arendt, A. A.; Arko, S.
Abstract: We determine the geodetic mass balance of surge‐type Black Rapids Glacier, Alaska, for the time periods 1980–2001 and 2001–2010 by combining modern interferometric synthetic aperture radar (InSAR)‐derived digital elevation models (DEMs), DEMs derived from archival aerial imagery, laser altimetry data, and in situ surface elevation measurements. Our analysis accounts for both the large rockslides and terrain displacements caused by the 2002 M 7.9 earthquake on the Denali fault, which runs through Black Rapids Glacier. To estimate uncertainties, we apply Monte Carlo simulations. For the earthquake‐triggered rockslides we find a volume of 56.62 ± 2.86 × 10 6 m 3, equivalent to an average debris thickness of 4.44 ± 0.24 m across the 11.7 km 2 deposit area on the glacier. Terrain displacement due to the earthquake corresponds to an apparent glacier volume change of −53.1 × 10 6 m 3, which would cause an apparent specific mass balance of −0.19 meter water equivalent (mwe) if not taken into account. The geodetic mass balance of Black Rapids Glacier is −0.48 ± 0.07 mwe a −1 for the entire 30 year period, but more negative for the period 2001–2010 (−0.64 ± 0.11 mwe a −1 ) than the period 1980–2001 (−0.42 ± 0.11 mwe a −1 ), in agreement with trends indicated by in situ mass balance measurements. Elevation data indicate no net thickening of the surge reservoir between 1980 and 2010, in contrast to what is expected during the quiescent phase. A surge of Black Rapids Glacier in the near future is thus considered unlikely. Key Points: Annual mass balances of Black Rapids Glacier are more negative over the period 2001–2010 than 1980–2001 A surge of Black Rapids Glacier in the near future is unlikely given the absence of thickening in the surge reservoir Apparent glacier volume changes due to the rockslide deposits and earthquake displacements can be substantial